Impact of Media Literacy and Media Technology on Agenda-Setting A Case Study of Broadcast Media in Pakistan: Muhammad Riaz Raza,Aslam Parvez (PJDOL, 2023)
Four major issues Pak-US relations, Energy crises, Law and order and National reconciliation ordinance were studied on two mainstream channels, Express and Geo News to explore media public association in the light of media literacy and media technology. Randomly selected bulletins and commentary talk shows for one year have been examined togauge the role of media education and media technologies on media agenda while a survey to 500 cable television viewers of two news channels has been conducted separately to check the audience’s agenda on these issues. Overall, 156 news bulletins and the same number of prime time talk shows were analyzed in the light of agenda setting and media literacy models. Results have confirmed the strong connectionsbetween media’s issues salience and audience’s issue priorities on four understudied issues. Correlations were measured from >0.67 to >0.92with p value less than .001.